Qualitative data analysis : practical strategies - Bazeley, Pat (London Sage, 2021)
"This book takes a practical approach to all the steps involved in planning and conducting qualitative data analysis. Balancing theoretical foundations with applied advice, it helps you develop a systematic approach to your analysis. It demonstrates the importance of tying analysis into every aspect of research, from design, through data collection and management, to writing up, and provides step-by-step guidance on how to embed analysis from the start. Grounded in the reality of doing research, the book
Keywords: Social sciences -- Research -- Data processing; Qualitative research; Social sciences -- Statistical methods; Social sciences -- Research